Long Noncoding RNA DANCR Activates Wnt/β-Catenin Signaling through MiR-216a Inhibition in Non-Small Cell Lung Cancer - Yu, Justine E. (Biomolecules, 2020)
Long noncoding RNA differentiation antagonizing nonprotein coding RNA (lncRNA-DANCR) is associated with poor prognosis in multiple cancers, and promotes cancer stemness and invasion. However, the exact mechanisms by which DANCR promotes non-small cell lung cancer (NSCLC) remain elusive. In this study, we determined that DANCR knockdown (KD) impeded cell migration and reduced stem-like characteristics in two NSCLC cell lines, A549 and H1755. Wnt signaling was shown to promote NSCLC proliferation, stemness, and invasion; therefore, we hypothesized that DANCR may regulate these activities through induction of the Wnt/β-catenin pathway. DANCR KD reduced β-catenin signaling and protein expression, and decreased the expression of β-catenin gene targets c-Myc and Axin2. One of the well-defined functions of lncRNAs is their ability to bind and inhibit microRNAs. Through in silico analysis, we identified tumor suppressor miR-216a as a potential binding partner to DANCR, and confirmed this binding through coimmunoprecipitation and luciferase-reporter assays. Furthermore, we show that DANCR-induced β-catenin protein expression may be blocked with miR-216a overexpression. Our findings illustrate a role of DANCR in NSCLC migration and stemness, and suggest a novel DANCR/miR-216a signaling axis in the Wnt/β-catenin pathway.